Pre-sodium-modified coal-based hard carbon negative electrode material as well as preparation method and application thereof

By using pre -sodium coal -based hard carbon negative materials in sodium ion batteries, the use of alkaline activation and liquid phase composite technology to form a closed structure, solving the problem of active sodium loss during the first charging and discharge process of hard carbon. Efficient battery performance improvement.

CN119340355APending Publication Date: 2025-01-21CARBON ONE NEW ENERGY GRP CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411143692.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the first charge and discharge process of the hard carbon anode material in existing sodium ion batteries, a large amount of active sodium loss caused by the formation of solid electrolyte interface phase (SEI), reducing the first-time Coulomb efficiency of the battery.

Method used

The pre -sodium coal -based hard carbon negative material is used. The material is used to make a microporous structure in the coal -based powder material through alkaline activation, and the liquid phase composite with sodium salt is compounded. Reduce the formation of SEI and improve sodium storage.

Benefits of technology

It effectively improves the first Coulomb efficiency and charge and discharge capacity of the battery, reduces operating risks and production costs, and improves the cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340355A_ABST
    Figure CN119340355A_ABST
Patent Text Reader

Abstract

The invention provides a pre-sodium-modified coal-based hard carbon negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing a coal-based powder material and strong alkali in water, and heating and stirring until a first colloidal mixture is obtained; s2, in an inert atmosphere, drying the first colloidal mixture, and performing first carbonization to obtain an intermediate; s3, performing cleaning and ultrasonic treatment on the intermediate, mixing the intermediate with sodium salt in water, and performing heating and stirring until a second colloidal mixture is obtained; and S4, in an inert atmosphere, drying the second colloidal mixture, carrying out second carbonization, and cleaning to obtain the pre-sodium-modified coal-based hard carbon negative electrode material. A large number of micropore structures are manufactured in the coal-based powder material through alkali activation, then the micropore structures and the sodium salt are subjected to liquid-phase compounding, micropores are converted into closed pore structures in the subsequent high-temperature carbonization process, and the first coulombic efficiency and the charge and discharge capacity of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular, relates to a pre-sodiumized coal-based hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] As the global demand for clean energy grows, sodium-ion batteries, as a new type of battery technology, have attracted widespread attention due to their advantages such as abundant resources, low cost and high safety. Among them, hard carbon is a carbon material with high specific surface area and good electrochemical stability, which is widely used as the negative electrode material of sodium-ion batteries. However, during the first charge and discharge process of hard carbon negative electrode materials, due to the formation of more solid electrolyte interface phase (SEI), a large amount of active sodium will be lost, resulting in a low first coulombic efficiency of the battery.

[0003] At present, the first coulombic efficiency of hard carbon negative electrode materials is mainly improved by pre-sodiumization technology. Pre-sodiumization technology refers to the process of pre-embedding sodium ions into hard carbon negative electrode materials by a certain method before battery assembly, thereby reducing the loss of active sodium during the first charge and discharge process and improving the first coulombic efficiency of the battery. Although the existing pre-sodiumization technology can improve the first coulombic efficiency of hard carbon negative electrode materials to a certain extent, there are still some problems. First, the pre-sodiumization process often requires the use of a highly active sodium source, such as metallic sodium, which not only increases the danger of operation, but also increases production costs. Secondly, the control of the pre-sodiumization process is difficult. If the amount of sodium pre-embedded is insufficient, the first coulombic efficiency of the battery cannot be effectively improved; if the amount of sodium pre-embedded is too large, the battery's cycle performance may decrease. Therefore, there is still a need to develop safe, simple, effective and controllable methods to improve the first coulombic efficiency of hard carbon materials.

[0004] The contents of the background technology section are merely the technologies known to the inventors and do not necessarily represent the prior art in the field. Summary of the invention

[0005] The purpose of the present invention is to improve the initial charge and discharge capacitance and coulomb efficiency of a sodium ion battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a pre-sodiumized coal-based hard carbon negative electrode material. The pre-sodiumized coal-based hard carbon negative electrode material comprises closed pores, wherein the closed pores comprise sodium ions, and the pore volume of the closed pores is 0.1 to 0.5 cm 3 / g.

[0007] The pre-sodiumized coal-based hard carbon negative electrode material provided in the present application includes closed pores, and the closed pores include sodium ions. That is, the sodium salt introduced by pre-sodiumization is filled in these closed pores. The closed-pore structure can reduce the formation of SEI, and is conducive to the filling of sodium ions, thereby improving the sodium storage capacity of the material. Therefore, during the first charge and discharge process of the battery, the pre-sodiumized coal-based hard carbon negative electrode material can provide more active sodium, thereby effectively improving the first coulombic efficiency and charge and discharge capacity of the battery.

[0008] In some embodiments of the present application, the pre-sodiumized coal-based hard carbon negative electrode material satisfies at least one of the following conditions:

[0009] a) the sodium content of the pre-sodiumized coal-based hard carbon negative electrode material is 1 to 8%;

[0010] b) The median particle size D of the pre-sodiumized coal-based hard carbon negative electrode material 50 ≤10μm; optionally 5-7μm;

[0011] c) The specific surface area of ​​the pre-sodiumized coal-based hard carbon negative electrode material is ≤10cm 2 / g; optionally 4 to 6 cm 2 / g;

[0012] d) The carbon interlayer spacing d of the pre-sodiumized coal-based hard carbon negative electrode material 002 ≥0.35nm; optionally 0.37~0.39nm;

[0013] e) the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the pre-sodiumized coal-based hard carbon negative electrode material I D / I G It is 1.15~1.80.

[0014] The pre-sodiumized coal-based hard carbon negative electrode material under the above conditions has better performance and is more conducive to improving the initial charge and discharge capacity and coulombic efficiency of sodium ion batteries.

[0015] The second aspect of the present application provides a method for preparing a pre-sodiumized coal-based hard carbon negative electrode material, comprising the following steps:

[0016] S1: mixing the coal-based powder material and the strong alkali in water, heating and stirring until a first colloidal mixture is obtained;

[0017] S2: Under an inert atmosphere, drying the first colloidal mixture and then performing a first carbonization to obtain an intermediate;

[0018] S3: washing and ultrasonicating the intermediate and mixing it with sodium salt in water, heating and stirring until a second colloidal mixture is obtained;

[0019] S4: Under an inert atmosphere, the second colloidal mixture is dried, subjected to a second carbonization, and then washed to obtain the pre-sodiumized coal-based hard carbon negative electrode material.

[0020] This application creates a large number of microporous structures in coal-based powder materials through alkali activation, and then liquid-phase composites with sodium salts. The micropores are transformed into closed-pore structures during the subsequent high-temperature carbonization process. The closed-pore structure can reduce the formation of SEI, and is conducive to the filling of sodium ions and improving the sodium storage capacity of the material. Therefore, during the first charge and discharge process of the battery, the pre-sodiumized coal-based hard carbon negative electrode material can provide more active sodium, thereby effectively improving the first coulombic efficiency and charge and discharge capacity of the battery.

[0021] In some embodiments of the present application, the preparation method further comprises:

[0022] S0: washing the coal-based material, drying it and crushing it to obtain the coal-based powder material;

[0023] Optionally, the median particle size D of the coal-based powder material is 50 4~8μm;

[0024] Optionally, in step S0, the drying temperature is 80-120° C. and the drying time is 12-36 hours.

[0025] The coal-based powder material used in the present application may also be commercially available. The coal-based powder material within the above particle size range reacts with alkali to obtain micropores with higher porosity, thereby obtaining more closed pores in the subsequent reaction stage.

[0026] In some embodiments of the present application, in step S1, the strong base is solid KOH and / or NaOH;

[0027] Optionally, the mass ratio of the coal-based powder material to the strong alkali is (1-10):1;

[0028] Optionally, the heating in step S1 is water bath heating;

[0029] Further optionally, the water bath heating temperature is 60-100°C.

[0030] In this step, a strong base is used to react with the coal-based powder material to remove impurities such as silicon and alkali metal salts in the coal-based powder material, thereby generating a large number of micropores in the coal-based powder material. When a colloid (referred to as the first colloid in this application) is generated, the reaction is basically completed.

[0031] In some embodiments of the present application, in step S2, the intermediate has micropores, and the average pore size of the micropores is 0.2 to 1 nm;

[0032] Optionally, the average pore size of the micropores is 0.5 to 0.8 nm;

[0033] Optionally, the first carbonization temperature is 700-900°C, the heating rate is 1-10°C / min, and the holding time is 1-4h;

[0034] Optionally, the drying temperature in step S2 is 80-120°C.

[0035] In this step, the first colloid is first dried and then carbonized to obtain an intermediate with micropores, so that sodium salt can be introduced later. Drying first and then carbonizing is conducive to the formation of micropores. The carbonization in this step also has an activation effect.

[0036] In some embodiments of the present application, in step S3, the mass ratio of the intermediate to the sodium salt is (10-50):1;

[0037] Optionally, the sodium salt includes one or more of sodium carbonate, sodium bicarbonate, sodium chloride, sodium acetate, and sodium fluoride;

[0038] Optionally, the ultrasound time is 1 to 5 hours;

[0039] Optionally, the intermediate is cleaned by a combination of acid washing and water washing, and then dried;

[0040] Further optionally, the acid used for pickling is HCl, the concentration of HCl is 1-6 mol / L, the pickling time is 6-12 h, and the drying temperature is 80-120°C.

[0041] In this step, the intermediate with a large number of micropores is cleaned and reacted with sodium salt to introduce sodium ions, which can be complexed with oxygen-containing groups such as hydroxyl and carboxyl groups in the micropores to fill the micropores. When a colloid is formed, it indicates that the complexation process of sodium ions is basically completed.

[0042] In some embodiments of the present application, in step S4, the temperature of the second carbonization is 1000-1400°C, the heating rate is 1-10°C / min, and the holding time is 1-6h;

[0043] Optionally, the drying temperature in step S4 is 80-120°C.

[0044] Optionally, the drying temperature in step S4 is 80-120°C.

[0045] In this step, the second colloidal mixture is carbonized. During the high-temperature carbonization process, carbon microcrystals will grow. As the carbon microcrystals grow, the micropores can be blocked, thereby converting the open micropores into closed pores. In the negative electrode material thus prepared, the sodium ions are located in the closed pores.

[0046] The third aspect of the present application provides a negative electrode sheet, which includes any of the pre-sodiumized coal-based hard carbon negative electrode materials described above, or a pre-sodiumized coal-based hard carbon negative electrode material prepared by any of the preparation methods described above.

[0047] A fourth aspect of the present application provides a sodium ion battery, which includes the above-mentioned negative electrode sheet;

[0048] Optionally, the first coulombic efficiency of the sodium ion battery is ≥87%;

[0049] Optionally, the first charging capacity of the sodium ion battery is greater than 310 mAh / g, and the first discharging capacity of the sodium ion battery is greater than 340 mAh / g.

[0050] The sodium ion battery provided in the present application has very good first charge and discharge capacity and first coulombic efficiency.

[0051] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The accompanying drawings constituting a part of the present disclosure are used to provide a further understanding of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute improper limitations on the present disclosure.

[0053] Figure 1 This is a process flow chart for preparing a pre-sodiumized coal-based hard carbon negative electrode material provided in one embodiment of the present application.

[0054] Figure 2 This is a process flow chart for preparing a pre-sodiumized coal-based hard carbon negative electrode material provided in another embodiment of the present application.

[0055] Figure 3 This is a SEM image of the pre-sodiumized coal-based hard carbon negative electrode material prepared in Example 1 of the present application.

[0056] Figure 4 This is the first charge and discharge curve diagram of the coal-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0057] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0058] The disclosure below provides many different embodiments or examples for implementing the present invention. In order to simplify the disclosure of the present invention, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplicity and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific examples of processes and materials, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0059] In addition, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the present invention, and will not be interpreted in an idealized or overly formal sense unless explicitly defined in this article.

[0060] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation from the particular value as determined by one skilled in the art, taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0061] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0062] The pre-sodiumized coal-based hard carbon negative electrode material provided in the present application includes closed pores, and the closed pores include sodium ions. That is, the sodium salt introduced by pre-sodiumization is filled in these closed pores. The closed-pore structure can reduce the formation of SEI, and is conducive to the filling of sodium ions and improves the sodium storage capacity of the material. Therefore, during the first charge and discharge process of the battery, the pre-sodiumized coal-based hard carbon negative electrode material can provide more active sodium, thereby effectively improving the first coulombic efficiency and charge and discharge capacity of the battery.

[0063] In this application, the pore volume of the closed pore is 0.1 to 0.5 cm 3 / g. Within this pore volume range, the pre-sodiumized coal-based hard carbon negative electrode material can have an appropriate amount of sodium ions, so the first coulombic efficiency of the prepared sodium ion battery is better. In some specific embodiments, the pore volume of the closed pore can be 0.1cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g or 0.5cm 3 / g.

[0064] Optionally, the sodium content of the pre-sodiumized coal-based hard carbon negative electrode material provided in the present application is 1-8%. Under the above pre-sodium amount, the first coulombic efficiency of the sodium ion battery can be more effectively improved. In some specific embodiments, the sodium content may be 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%.

[0065] Optionally, the median particle size D of the pre-sodiumized coal-based hard carbon negative electrode material provided in the present application is 50 ≤10μm. The smaller the particle size, the better the performance of the negative electrode material. Further, the median particle size D 50 In some specific embodiments, the median particle size D 50 It can be 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, 4μm, 3μm or 2μm.

[0066] Optionally, the specific surface area of ​​the pre-sodiumized coal-based hard carbon negative electrode material provided in the present application is ≤10cm 2 / g. Smaller specific surface area, fewer surface defects, better performance of negative electrode materials. Further optional 4 to 6 cm 2 In some specific embodiments, the specific surface area may be 10 cm 2 / g, 9cm 2 / g, 8cm 2 / g, 7cm 2 / g, 6cm 2 / g, 5cm 2 / g, 4cm 2 / g, 3cm 2 / g or 2cm 2 / g.

[0067] Optionally, the carbon interlayer spacing d of the pre-sodiumized coal-based hard carbon negative electrode material provided in the present application is 002 ≥0.35nm. A large carbon interlayer spacing is conducive to providing more sodium storage sites. Further, optionally, the carbon interlayer spacing d 002 In some specific embodiments, the carbon layer spacing d 002It may be 0.36nm, 0.37nm, 0.38nm, 0.39nm, 0.40nm, 0.41nm or 0.42nm.

[0068] Optionally, the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the pre-sodiumized coal-based hard carbon negative electrode material provided in the present application is D / I G In some specific embodiments, the intensity ratio of the amorphous carbon peak to the graphitized carbon peak is 1.15 to 1.80. D / I G It can be 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.75 or 1.80.

[0069] The pre-sodiumized coal-based hard carbon negative electrode material provided in the present application includes a large number of closed pores, which are filled with an appropriate amount of sodium salt, thereby effectively improving the first coulombic efficiency of the sodium ion battery.

[0070] The present application further provides a method for preparing a pre-sodiumized coal-based hard carbon negative electrode material, such as Figure 1 As shown, the process includes the following steps S1 to S4.

[0071] S1: Mix the coal-based powder material and the strong alkali in water, and heat and stir until a first colloidal mixture is obtained.

[0072] In this step, a strong alkali is used to react with the coal-based powder material, thereby removing impurities such as silicon and alkali metal salts in the coal-based powder material, thereby generating a large number of micropores in the coal-based powder material. When a colloid (referred to as the first colloid in this application) is generated, it means that the reaction is basically completed. The colloid includes aluminosilicate gel.

[0073] Optionally, the coal-based powder used in the present application includes anthracite, bituminous coal, lignite, etc. Optionally, the median particle size D of the coal-based powder material used is 50 The median particle size D of the coal-based powder material used in the above particle size range is 4 to 8 μm. When the coal-based powder material reacts with alkali, the porosity of the micropores obtained is higher, so that more closed pores can be obtained in the subsequent reaction stage. 50 It may be 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm.

[0074] Optionally, the strong alkali used is solid KOH and / or NaOH. These two alkalis have better reactivity and can generate a large number of micropores in the coal-based powder material.

[0075] Optionally, the mass ratio of the coal-based powder material to the strong alkali is (1-10):1. Within this range, more micropores can be obtained without wasting alkali. In some specific embodiments, the mass ratio of the coal-based powder material to the strong alkali can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.

[0076] Optionally, the heating is water bath heating. Further optionally, the temperature of the water bath heating is 60-100°C. Water bath heating is evenly heated and has good temperature control. In this temperature range, the coal-based powder material and the alkali can react well. In some specific embodiments, the temperature of the water bath heating can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0077] Optionally, the method provided in the present application may further include a step S0 of preparing a coal-based powder material: washing the coal-based material, drying and crushing the coal-based powder material to obtain a coal-based powder material, such as Figure 2 Of course, the coal-based powder material used in this application can also be commercially available.

[0078] Optionally, the drying temperature in step S0 is 80-120° C., and the time is 12-36 hours. In some specific embodiments, the drying temperature may be 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., or 120° C. In some specific embodiments, the drying time may be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, or 36 hours.

[0079] S2: Under an inert atmosphere, the first colloidal mixture is dried and then subjected to a first carbonization to obtain an intermediate.

[0080] In this step, the first colloid is first dried and then carbonized to obtain an intermediate with micropores, so that sodium salt can be introduced later. Drying first and then carbonizing is conducive to the formation of micropores. The carbonization in this step also has an activation effect.

[0081] Optionally, the average pore size of the obtained micropores is 0.2-1 nm, further optionally 0.5-0.8 nm. In some specific embodiments, the average pore size of the micropores may be 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm or 0.8 nm.

[0082] Optionally, the drying temperature in step S2 is 80-120° C. In some specific embodiments, the drying temperature may be 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C. or 120° C.

[0083] Optionally, the temperature of the first carbonization is 700-900°C, the heating rate is 1-10°C / min, and the holding time is 1-4h. A slow heating rate is conducive to the formation of micropores. In some specific embodiments, the temperature of the first carbonization may be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or 900°C. In some specific embodiments, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min. In some specific embodiments, the holding time may be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h.

[0084] Optionally, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0085] S3: The intermediate is washed and ultrasonicated and mixed with sodium salt in water, and heated and stirred until a second colloidal mixture is obtained.

[0086] In this step, the intermediate with a large number of micropores is cleaned and reacted with sodium salt to introduce sodium ions, which can react with oxygen-containing functional groups in the micropores to fill the micropores. When a colloid is formed, it indicates that the complexation process of sodium ions is basically completed.

[0087] Optionally, the sodium salt includes one or more of sodium carbonate, sodium bicarbonate, sodium chloride, sodium acetate, and sodium fluoride. The present application uses inorganic sodium salt for pre-sodiumization, avoiding the use of highly active sodium sources such as metallic sodium, thereby reducing the danger of operation. In addition, sodium salt is low in cost and abundant in resources, making the manufacture of sodium ion batteries more economical.

[0088] Optionally, in step S3, the mass ratio of the intermediate to the sodium salt is (10-50):1. Too much or too little sodium salt introduced is not good for the charge and discharge capacity and the first coulombic efficiency of the sodium ion battery. In some specific embodiments, the mass ratio of the intermediate to the sodium salt can be 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1.

[0089] Optionally, the intermediate is cleaned by a combination of pickling and water washing, and then dried. Pickling can further react with impurities in the coal-based material, and more micropores can be generated in the material while removing impurities. After pickling, wash with water until neutral, and then dry. Further optionally, the acid used for pickling is HCl, which has a better impurity removal effect. The concentration of HCl may be 1 to 6 mol / L. In some specific embodiments, the concentration of HCl may be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L. Optionally, the pickling time is 6 to 12 h. In some specific embodiments, the pickling time may be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h. Optionally, the drying temperature in step S3 is 80 to 120 ° C. In some specific embodiments, the drying temperature may be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.

[0090] Optionally, the ultrasonic time is 1 to 5 hours. The purpose of ultrasound is to fully disperse the cleaned intermediate so that the micropores of the intermediate are filled with sodium salt. In some specific embodiments, the ultrasonic time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours. The ultrasonic frequency can be arbitrary.

[0091] S4: Under an inert atmosphere, the second colloidal mixture is dried and then carbonized for the second time, and then washed to obtain a pre-sodiumized coal-based hard carbon negative electrode material.

[0092] In this step, the second colloidal mixture is carbonized. During the high-temperature carbonization process, carbon microcrystals will grow. As the carbon microcrystals grow, the micropores can be blocked, thereby converting the open micropores into closed pores. In the negative electrode material thus prepared, the sodium ions are located in the closed pores. Under the triple drive of high-temperature thermal driving force and the adsorption force provided by oxygen-containing functional groups (C=O and -COOH, etc.) and defect sites, the sodium ions in the closed pores will be pre-stored in the oxygen-containing functional groups and defect sites, thereby eliminating the additional consumption of the electrolyte by the oxygen-containing functional groups and defect sites during the discharge process, achieving the effect of in-situ pre-sodiumization, thereby improving the first coulomb efficiency and the charge and discharge capacity of the sodium ion battery.

[0093] In this step, the carbonization is followed by another cleaning process, which can wash away the sodium salt on the surface of the material, while the sodium salt in the closed pores will not be washed away. The sodium salt on the surface of the material will react with the electrolyte during the charge and discharge process, occupying part of the capacity and causing the material's capacity to decrease.

[0094] Optionally, the temperature of the second carbonization is 1000-1400°C, the heating rate is 1-10°C / min, and the holding time is 1-6h. The heating rate in this step is slow, and a relatively stable closed-cell structure can be formed, which will not cause the product to expand too fast due to the heating rate being too fast, thereby affecting the final product. In some specific embodiments, the temperature of the second carbonization may be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C or 1400°C. In some specific embodiments, the heating rate of the second carbonization may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min. In some specific embodiments, the holding time may be 1h, 2h, 3h, 4h, 5h or 6h.

[0095] Optionally, the drying temperature in this step is 80-120° C. In some specific embodiments, the drying temperature may be 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C. or 120° C.

[0096] This application creates a large number of microporous structures in coal-based powder materials through alkali activation, and then liquid-phase composites with sodium salts. The micropores are transformed into closed-pore structures during the subsequent high-temperature carbonization process. The closed-pore structure can reduce the formation of SEI, and is conducive to the filling of sodium ions, thereby improving the sodium storage capacity of the material. Therefore, during the first charge and discharge process of the battery, the pre-sodiumized coal-based hard carbon negative electrode material can provide more active sodium, thereby effectively improving the first coulombic efficiency and charge and discharge capacity of the battery.

[0097] The present application further provides a negative electrode sheet, comprising the above-mentioned pre-sodiumized coal-based hard carbon negative electrode material or the pre-sodiumized coal-based hard carbon negative electrode material prepared by the above-mentioned preparation method.

[0098] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer may include the above-mentioned pre-sodiumized coal-based hard carbon negative electrode material.

[0099] The current collector may be a metal foil, such as an aluminum foil, a copper foil, etc., preferably a copper foil. The negative electrode film layer may further include a binder, a conductive agent, etc. The binder may be, for example, styrene-butadiene rubber (SBR), polyvinylidene chloride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC-Na), sodium alginate, etc. The conductive agent may be, for example, graphene, carbon nanotubes, Ketjen black, conductive carbon black (SP), etc. Optionally, the negative electrode film layer may further include other additives, such as a dispersant (e.g., carboxymethyl cellulose (CMC)), etc.

[0100] The present application also provides a sodium ion battery, which includes the above-mentioned negative electrode sheet. The sodium ion battery also includes a positive electrode sheet, a separator and an electrolyte.

[0101] Optionally, the sodium ion battery has an initial charge capacity of >310 mAh / g. Optionally, the sodium ion battery has an initial discharge capacity of >340 mAh / g. Optionally, the sodium ion battery has an initial coulombic efficiency of ≥87%.

[0102] The sodium ion battery of the present application is a secondary battery, which refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0103] The sodium ion battery provided in the present application has very good first charge and discharge capacity and first coulombic efficiency.

[0104] The present invention will be described below with reference to specific embodiments. The process condition values ​​taken in the following embodiments and comparative examples are exemplary, and their possible numerical ranges are as shown in the aforementioned summary of the invention. For process parameters not particularly noted, conventional techniques can be used. Unless otherwise specified, reagents and instruments used in the technical scheme provided by the present invention can be purchased from conventional channels or the market. It should be noted that, in the absence of conflict, the features in the embodiments in this application and the embodiments can be combined with each other.

[0105] Example 1

[0106] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0107] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0108] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0109] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0110] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.5 g of solid sodium carbonate was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0111] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0112] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details. The SEM image of the pre-sodiumized coal-based hard carbon negative electrode material prepared in this embodiment is shown in Figure 3 .

[0113] In this embodiment and the comparative examples below, the material was subjected to adsorption and desorption test by BET to obtain the specific surface area, pore volume, porosity, and average pore size of the closed pores of the material; the median particle size (D50) of the sample was tested by a laser particle size analyzer; the sodium content in the material was measured by an organic element analyzer (EA); the carbon interlayer spacing of the material was measured by XRD; the intensity ratio (I D / I G ) for determination.

[0114] Example 2

[0115] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0116] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0117] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0118] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0119] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.2 g of solid sodium bicarbonate was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0120] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0121] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0122] Example 3

[0123] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0124] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material with a particle size of about 5 μm.

[0125] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0126] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0127] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 1 g of solid sodium carbonate was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0128] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0129] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0130] Example 4

[0131] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0132] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0133] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0134] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0135] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.5 g of solid sodium chloride was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0136] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1200°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0137] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0138] Example 5

[0139] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0140] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0141] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0142] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0143] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.5 g of solid sodium acetate was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0144] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1400°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0145] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0146] Example 6

[0147] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0148] (1) Wash a certain amount of bituminous coal with water three times, dry it in a forced air drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0149] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0150] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0151] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.5 g of solid sodium fluoride was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0152] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0153] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0154] Example 7

[0155] This embodiment prepares a pre-sodiumized coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0156] (1) A certain mass of lignite was washed with water three times, dried in a blast drying oven at 105°C, and then crushed to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0157] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0158] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0159] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105° C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.7 g of solid Na2CO3 was weighed and added thereto, heated in a water bath at 80° C. and stirred until a gelatinous state was obtained, to obtain a second gelatinous mixture;

[0160] (5) The second colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0161] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained pre-sodiumized coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0162] Comparative Example 1

[0163] This comparative example prepares a coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0164] (1) Wash a certain amount of anthracite with water three times, dry it in a blast drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0165] (2) The coal-based powder material and solid KOH were weighed in a mass ratio of 2:1 and added into 100 mL of deionized water. The mixture was placed in a water bath and heated at 80° C. and stirred until it became a gelatinous mixture, thereby obtaining a first gelatinous mixture.

[0166] (3) The first colloidal mixture was placed in a forced air drying oven and dried at 80° C., and then heated to 800° C. at a rate of 5° C. / min in a nitrogen atmosphere, and then kept at this temperature for 2 h. After the first carbonization was completed, the temperature was lowered to room temperature to obtain an intermediate.

[0167] (4) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105°C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h.

[0168] (5) The intermediate after ultrasonic treatment is placed in a forced air drying oven at 80°C for drying, and then heated to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, it is repeatedly washed in running water for 3 times and then placed in a forced air drying oven for drying at 105°C to obtain the intermediate.

[0169] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0170] Comparative Example 2

[0171] This comparative example prepares a coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0172] (1) Wash a certain amount of bituminous coal with water three times, dry it in a forced air drying oven at 105°C, and then crush it to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0173] (2) The coal-based powder material is heated to 800°C at a rate of 5°C / min under a nitrogen atmosphere, then kept at this temperature for 2 hours, and after the first carbonization is completed, the temperature is cooled to room temperature to obtain an intermediate.

[0174] (3) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105°C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h.

[0175] (4) The intermediate after ultrasonic treatment is placed in a forced air drying oven at 80°C for drying, and then heated to 1300°C at 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, it is repeatedly washed in running water for 3 times and then placed in a forced air drying oven for drying at 105°C to obtain the intermediate.

[0176] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0177] Comparative Example 3

[0178] This comparative example prepares a coal-based hard carbon negative electrode material, and the specific steps are as follows:

[0179] (1) A certain mass of lignite was washed with water three times, dried in a blast drying oven at 105°C, and then crushed to obtain the median particle size D 50 It is a coal-based powder material of about 5μm.

[0180] (2) The coal-based powder material is heated to 800°C at a rate of 5°C / min under a nitrogen atmosphere, then kept at this temperature for 2 hours, and after the first carbonization is completed, the temperature is cooled to room temperature to obtain an intermediate.

[0181] (3) 20 g of the intermediate was added to a 2 mol / L HCL solution and acidified for 8 h, then washed repeatedly with deionized water until neutral, and then dried in a forced air drying oven at 105°C. 10 g of the dried intermediate was weighed and added to 100 mL of deionized water and ultrasonicated for 2 h, and then 0.5 g of solid sodium carbonate was weighed and added thereto, heated in a water bath at 80°C and stirred until a gelatinous mixture was obtained;

[0182] (5) The colloidal mixture is placed in a forced air drying oven and dried at 80°C. Then, the temperature is raised to 1300°C at a rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours. After the second carbonization is completed, the mixture is repeatedly washed with running water for three times and then placed in a forced air drying oven and dried at 105°C.

[0183] The specific surface area, pore volume, median particle size (D50) and other parameters of the obtained coal-based hard carbon negative electrode material were measured. See Table 1 for details.

[0184] Experimental example

[0185] The coal-based hard carbon negative electrode materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were assembled into batteries respectively. The specific steps are as follows: the obtained negative electrode material, conductive agent Super P, dispersant CMC, and binder styrene-butadiene rubber (SBR) were mixed in a mass ratio of 94.5:2:1.5:2 to prepare a slurry; the negative electrode slurry was coated on aluminum foil with a scraper of about 75 μm, dried in a blast drying oven for about 4 hours, and dried in a vacuum drying oven for 12 hours. After rolling and cutting, a hard carbon electrode pole piece was obtained. After the pole piece was placed in a vacuum drying oven and dried for 1 hour, it was transferred to an argon atmosphere glove box and assembled into a C2032 button battery in the order of "negative electrode shell → pole piece → diaphragm → electrolyte → glass fiber → electrolyte → sodium sheet → gasket → shrapnel → positive electrode shell". The electrolyte contains 1.5 mol / L sodium salt (NaPF6), the solvent is ethylene carbonate (EC, 99.9%), dimethyl carbonate (DMC, 99.9%), ethylene glycol dimethyl ether (DME, 99.9%), the metal sodium sheet is the counter electrode, and the diaphragm is glass fiber filter paper.

[0186] The prepared button battery was subjected to charge and discharge cycles, and the charge and discharge conditions were as follows: the button battery was charged and discharged using a Blue Electric Battery Test System, with a voltage test range of 0.005 to 2V (vs. Na / Na+), and the discharge was discharged at 0.1C to 0.005V; the charge was charged at 0.1C to 2V, and the nominal capacity was set to 280mAh / g. The first charge capacity, first discharge capacity and first coulombic efficiency of the button battery were tested.

[0187] During battery assembly, five batteries were prepared for each test, and a total of five sets of data were tested. The final performance was the average of the five sets of data. Specific data are shown in Table 2. The first charge and discharge curves of the corresponding sodium ion batteries prepared from the coal-based hard carbon negative electrode materials of Example 1 and Comparative Example 1 are shown in Figure 4 .

[0188] Table 1

[0189]

[0190] Table 2

[0191]

[0192] As can be seen from Table 1, the closed pore volume of the pre-sodiumized coal-based hard carbon negative electrode material prepared in this application is 0.03-0.05 cm 3 / g, the present application uses alkali activation to produce a large number of microporous structures in the coal-based powder material, and then performs liquid phase compounding with sodium salt. The micropores are transformed into closed-pore structures during the subsequent high-temperature carbonization process, which is conducive to the filling of sodium ions. However, Comparative Examples 2 to 3 lack the step of alkali activation to produce micropores, so that the pore volume of the closed-pore coal-based hard carbon negative electrode material obtained is reduced to 0.01 or less, which is not conducive to the filling of sodium ions.

[0193] from Figure 3 It can be seen that the particle size of the pre-sodiumized coal-based hard carbon negative electrode material prepared in the present application is relatively uniform.

[0194] This application is conducive to the filling of sodium ions and improves the sodium storage capacity of the material. Therefore, during the first charge and discharge process of the battery, the pre-sodiumized coal-based hard carbon negative electrode material can provide more active sodium, thereby effectively improving the first coulomb efficiency and charge and discharge capacity of the battery. From Table 2 and Figure 4 It can be seen that the first charging capacity, first discharge capacity and first coulombic efficiency of the pre-sodiumized coal-based hard carbon negative electrode material prepared in the present application are relatively good, with the first efficiency being above 87%, while the overall performance of the coal-based hard carbon negative electrode materials prepared in Comparative Examples 1 to 3 is not very good.

[0195] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A pre-sodiumized coal-based hard carbon negative electrode material, characterized in that: The pre-sodiumized coal-based hard carbon negative electrode material comprises closed pores, wherein the closed pores contain sodium ions, and the pore volume of the closed pores is 0.1 to 0.5 cm 3 / g.

2. The pre-sodiumized coal-based hard carbon negative electrode material according to claim 1, characterized in that: The pre-sodiumized coal-based hard carbon negative electrode material meets at least one of the following conditions: a) the sodium content of the pre-sodiumized coal-based hard carbon negative electrode material is 1 to 8%; b) The median particle size D of the pre-sodiumized coal-based hard carbon negative electrode material 50 ≤10μm; optionally 5-7μm; c) The specific surface area of ​​the pre-sodiumized coal-based hard carbon negative electrode material is ≤10cm 2 / g; optionally 4 to 6 cm 2 / g; d) The carbon interlayer spacing d of the pre-sodiumized coal-based hard carbon negative electrode material 002 ≥0.35nm; optionally 0.37~0.39nm; e) the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the pre-sodiumized coal-based hard carbon negative electrode material I D / I G It is 1.15~1.

80.

3. A method for preparing a pre-sodiumized coal-based hard carbon negative electrode material, characterized in that: The following steps are involved: S1: mixing the coal-based powder material and the strong alkali in water, heating and stirring until a first colloidal mixture is obtained; S2: Under an inert atmosphere, drying the first colloidal mixture and then performing a first carbonization to obtain an intermediate; S3: washing and ultrasonicating the intermediate and mixing it with sodium salt in water, heating and stirring until a second colloidal mixture is obtained; S4: Under an inert atmosphere, the second colloidal mixture is dried, subjected to a second carbonization, and then washed to obtain the pre-sodiumized coal-based hard carbon negative electrode material.

4. The preparation method according to claim 3, characterized in that: Also includes: S0: washing the coal-based material, drying it and crushing it to obtain the coal-based powder material; Optionally, the median particle size D of the coal-based powder material is 50 4~8μm; Optionally, in step S0, the drying temperature is 80-120° C. and the drying time is 12-36 hours.

5. The preparation method according to claim 3, characterized in that: In step S1, the strong base is solid KOH and / or NaOH; Optionally, the mass ratio of the coal-based powder material to the strong alkali is (1-10):1; Optionally, the heating in step S1 is water bath heating; Further optionally, the water bath heating temperature is 60-100°C.

6. The preparation method according to claim 3, characterized in that: In step S2, the intermediate has micropores, and the average pore size of the micropores is 0.2 to 1 nm; Optionally, the average pore size of the micropores is 0.5 to 0.8 nm; Optionally, the first carbonization temperature is 700-900°C, the heating rate is 1-10°C / min, and the holding time is 1-4h; Optionally, the drying temperature in step S2 is 80-120°C.

7. The preparation method according to claim 3, characterized in that: In step S3, the mass ratio of the intermediate to the sodium salt is (10-50):1; Optionally, the sodium salt includes one or more of sodium carbonate, sodium bicarbonate, sodium chloride, sodium acetate, and sodium fluoride; Optionally, the ultrasound time is 1 to 5 hours; Optionally, the intermediate is cleaned by a combination of acid washing and water washing, and then dried; Further optionally, the acid used for pickling is HCl, the concentration of HCl is 1-6 mol / L, the pickling time is 6-12 h, and the drying temperature is 80-120°C.

8. The preparation method according to claim 3, characterized in that: In step S4, the temperature of the second carbonization is 1000-1400°C, the heating rate is 1-10°C / min, and the holding time is 1-6h; Optionally, the drying temperature in step S4 is 80-120°C.

9. A negative electrode sheet, characterized in that: It comprises the pre-sodiumized coal-based hard carbon negative electrode material as described in claim 1 or 2, or the pre-sodiumized coal-based hard carbon negative electrode material prepared by the preparation method as described in any one of claims 3 to 8.

10. A sodium ion battery, characterized in that: The negative electrode sheet according to claim 9; Optionally, the first coulombic efficiency of the sodium ion battery is ≥87%; Optionally, the first charging capacity of the sodium ion battery is greater than 310 mAh / g, and the first discharging capacity of the sodium ion battery is greater than 340 mAh / g.

Citation Information

Cited By

  • Sodium supplementing method of sodium ion battery hard carbon negative electrode material

    CN121215765A

  • Sodium pre-supplementing hard carbon negative electrode material as well as preparation method and application thereof

    CN122224808A